Audit committee expertise and political connection towards financial reporting quality with audit quality as a mediator in ASEAN - Dewi, I Gusti Ayu Ratih Permata; Suartana, I Wayan; Yasa, Gerianta Wirawan; Mimba, Ni Putu Sri Harta (International Journal of Management and Sustainability, 2025)
Internal oversight, specifically the work of the audit committee, and external oversight from external auditors can help minimize agency conflicts. Because the government acts as both a principal and an agent simultaneously, the agency relationship is complicated regarding government-owned enterprises. The quantitative approach used in this research involved selecting companies listed on the ASEAN Stock Exchange during the period from 2020 to 2022. A total of 620 firms were included in the sample, yielding 1,860 observations. Panel data regression analysis was employed. The results indicated that although the experience of the audit committee did not enhance audit quality, political connections had a positive effect. Additionally, the study revealed that audit quality served as a mediator in the relationship between the quality of political connections and the standard of financial reports, but it did not mediate the relationship between the competence of the audit committee and the quality of financial reports. The research findings are beneficial for prospective investors, as they should consider the existence of an audit committee, internal political connections, and the quality of audits, since these elements can improve the accuracy of financial statements.